A Study Of Customer/Passenger Perception On Online Airline Reservation Services In Malaysia - Lim, Wai Sheong (2007)
The introduction of the online airline reservation services is now very popular in the Malaysian airline industry. Due to the development of Information Communication Technology, the population of internet users have increased dramatically.